A clinicoepidemiological study of 50 cases of cutaneous tuberculosis in a tertiary care teaching hospital in Pokhara, Nepal - Dwari Binayak; Ghosh Arnab; Paudel Raju; Kishore P (Wolters Kluwer Medknow Publications, 2010)
Background: Cutaneous tuberculosis (TB) is essentially an invasion of the skin by Mycobacterium tuberculosis, the same bacteria that causes pulmonary tuberculosis. Aim: This study was conducted to study the common types of cutaneous TB and to find the management pattern in a tertiary teaching hospital in Pokhara, Nepal. Materials and Methods: All the cases of cutaneous TB were biopsied and furthermore investigated by performing Mantoux test, sputum examination, fine needle aspiration cytology, chest X-ray and ELISA. Results: In this study, we found that tuberculosis verrucous cutis (48%) had a higher incidence than other types of cutaneous TB. More males were affected than were females (1.2:1). Commonly affected sites were the limb and the buttock (48%). The most commonly affected age group was 16-25 years (40%). All cases (except two) were more than 15 mm in size in the Mantoux test. The histopathological picture was typical in all except three cases. All patients were treated with antitubercular treatment as per the national guidelines. Conclusion: The most common type of cutaneous TB was tuberculosis verrucous cutis and the most commonly affected sites were the limb and the buttock. As cutaneous TB sometimes reflects the presence of pulmonary tuberculosis, its incidence should not be ignored.